Serving the Public Interest - Thomas Markussen; Jean-Robert Tyran (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
We present a model of political selection in which voters elect a president from a set of candidates. We assume that some of the candidates are benevolent and that all voters prefer a benevolent president, i.e. a president who serves the public interest. Yet, political selection may fail in our model because voters cannot easily tell benevolent from egoistic candidates by observing their pre-election behavior. Egoistic types may strategically imitate benevolent types in the pre-election stage to extract rents once in office. We show that strategic imitation is less likely if the political system is likely to produce good governance. That is, if benevolent candidates are common, if the president has little discretionary power, and if the public sector is effective. We analyze the role of institutions like investigative media and re-election and show that they can improve or further hamper political selection, depending on the parameters of the political game.
Keywords: D64; D72; D82; H0; 330; Political selection; elections; social preferences; political leadership